PEDAGOGICAL POSSIBILITIES OF THE PROJECT-BASED TEACHING METHOD IN TECHNOLOGICAL EDUCATION. (Universal International Scientific Journal, 2026)
This article analyzes the basic laws of the science of educational technologies from a philosophical point of view. It also highlights the specific features of educational and upbringing technologies used in Western countries. In particular, the stages of development and the process of formation of educational technologies are scientifically examined. In addition, the methods of various levels used in educational technologies at the present time are interpreted on a scientific basis.
Keywords: pedagogical technology, pedagogical process, educational process, pedagogy, modern pedagogical technology, teaching technology, educational technology, educational method, educational methodology, pedagogical technique, pedagogical-technological process.